A Compact High-Gain Dual-Band Antenna for Ultrawideband Applications - Ali Khalid Jassim Al shamariy (Journal of Engineering and Sustainable Development)
This study deals with the extensive development of multiband antennas, compact in size and high in performance, to meet the requirements of modern wireless communication systems, namely the Ultrawideband (UWB) applications. This research presents the design of a Dual-Band Patch Antenna (DBPA) that works at 4.1 GHz and 6.7 GHz frequency ranges. This design offers a proposed solution to efficiently overcome the challenges of designing single-band microstrip patch antennas and the obstacles associated with the operation of conventional ones by achieving a noticeable increase in gain. The proposed antenna achieves a noticeable gain of approximately 10.227 dB at the frequency of 4.1 GHz and 4.982 dB at 6.7 GHz while achieving compact dimensions (65.2 mm 7 76.6 mm 1 1.6 mm) using an FR-4 substrate. In addition, the simulations show a fairly well-matched input impedance, a reflection coefficient of less than -10 dB, and a Voltage Standing Wave Ratio (VSWR) of less than 2 in both operating frequency ranges. The antenna also develops a uniform radiation pattern that suits various UWB communication applications. This performance is attributed to the good positioning and the appropriate dimensions of the rectangular slots, which leads to modifying the current path and focusing the surface wave, which enhances the gain and radiation efficiency.